Pre-operative withholding of infliximab and the risk of infections after major surgery in patients with rheumatoid arthritis - Ward, Michael M (Rheumatology (Oxford), 2020)
OBJECTIVES: Withholding TNF inhibitors (TNFI) before surgery has been recommended due to concern for post-operative infection. We examined the risks of post-operative infections and mortality in patients with RA in relation to the pre-operative timing of infliximab infusion. METHODS: In this population-based retrospective cohort study, we used US Medicare claims data from 2007 to 2015 to identify patients with RA who underwent coronary artery bypass grafting (CABG), aortic or vascular surgery, or bowel resection, and who were treated with infliximab in the 90 days prior to surgery. We examined associations between the timing of infusion and infections and mortality in the 30 days after surgery. We adjusted for the predicted probability of post-operative infection or death, demographic characteristics, use of MTX, post-operative blood transfusion and hospital volume. RESULTS: We studied 712 patients with CABG, 244 patients with vascular surgery and 862 patients with bowel resections. Post-operative pneumonia occurred in 7.4–11.9%, urinary tract infection in 9.0–15.2%, surgical site infection in 3.2–18.9%, sepsis in 4.2–9.6% and death in 3.5–7.0% among surgery cohorts. There was no association between the time from last infliximab dose to surgery and the risk of post-operative infection or mortality in any surgical cohort. No subgroups were identified that had an increased risk of infection with more proximate use of infliximab. CONCLUSION: Among elderly patients with RA, risks of infection and mortality after major surgery were not related to the pre-operative timing of infliximab infusion.